The Development of Online Learning Media by Using Moodle for General Chemistry Subject - Asyti Febliza; Oktariani Okatariani (Journal of Educational Science and Technology (EST), 2020)
This study aims to develop and obtain eligible online learning media by using moodle for general chemistry subjects by using moodle. In this study, flash animation and simulation were integrated as online media in moodle to attract students’ motivation. The topic in this moodle was a colloidal solution. The method of this study was the research and development method by using ADDIE model. Online learning media was validated by media and chemistry material experts, then the valid media presented to the 24 chemistry education students in Universitas Islam Riau to acquire responses toward online learning media. The results showed that online learning media is eligible and can be used as online learning media in which the average number of expert assessment reached higher than 80% with valid criteria. In addition, students’ responses toward online learning media by using moodle is positive in all aspects (interesting design; color, picture, and video preference; creativity and innovation; communication) with the average number of percentage more than 84% (good criteria). Overall, based on the results of online learning media by using moodle for general chemistry subject can be used as learning media to give students experience in online learning